2020
DOI: 10.1101/2020.11.24.20231324
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of SARS-CoV2 antibody Rapid Diagnostic Test kits (RDTs) and Real Time-Polymerase Chain Reaction (Rt-PCR) for COVID-19 Diagnosis in Kaduna, Nigeria

Abstract: The emergence of the RNA virus SARS-CoV2, the causative agent of COVID-19 and its declaration by the World Health Organization (WHO) as a pandemic has disrupted the delicate balance in health indices globally. Its attendant immune dysregulation and pathobiology is still evolving. Currently, real time PCR is the gold standard diagnostic test, however there are several invalidated antibody-based tests available for possible community screening. With ongoing community transmission in Nigeria, neither the true bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Consequently, Nigeria validated it during the screening of youth corps before their admission into the compulsory one-year national service [ 12 ]. Ige et al reported that although COVID-19 RDTs have lower sensitivity and specificity, they have proven useful in scaling up Nigeria’s COVID-19 testing system especially in schools, congregations, and hard-to-reach areas [ 13 ]. However, it is yet to be determined if the low sensitivity of RDTs contributed to the lower COVID-19 incidence in Nigeria.…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, Nigeria validated it during the screening of youth corps before their admission into the compulsory one-year national service [ 12 ]. Ige et al reported that although COVID-19 RDTs have lower sensitivity and specificity, they have proven useful in scaling up Nigeria’s COVID-19 testing system especially in schools, congregations, and hard-to-reach areas [ 13 ]. However, it is yet to be determined if the low sensitivity of RDTs contributed to the lower COVID-19 incidence in Nigeria.…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%
“…However, it is yet to be determined if the low sensitivity of RDTs contributed to the lower COVID-19 incidence in Nigeria. COVID-19 testing using RDTs should be conducted by qualified health care personnel while adhering strictly to COVID-19 protocols to avoid technical errors and further community spread of the SARS-CoV-2 [ 13 ].…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%
“…RDTs are cheaper and provide a faster TAT compared to the PCR, albeit with lower sensitivity and speci city. (30) RDTs have proven useful in scaling up SARS-CoV-2 laboratory testing capacity in Nigeria especially in closed population. The proportion of tests conducted with RDTs in Nigeria was observed to gradually increase as the pandemic progressed and was up to 15% by the end of September, 2021.…”
Section: Discussionmentioning
confidence: 99%